Pengembangan Visualisasi Layanan Perpustakaan Berbasis Desktop Virtual Reality untuk Edukasi Pengguna di Perpustakaan Universitas Negeri Malang - Sufi Malika Amalia; Adi Prasetyawan; Shamila Mohamed Shuhidan (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2026)
This study aims to develop a library service visualization using 3600 Virtual Reality as a user education medium at the Malang State University Library. Unlike previous studies that relied on head-mounted displays or conventional video-based orientation, this study develops an accessible desktop Virtual Reality platform integrated with AI-generated narration, enabling immersive user education without additional hardware. The research addresses the lack of interactive orientation media and the high frequency of repetitive technical inquiries regarding library services. Utilizing the Research and Development (R&D) method with the Borg and Gall model, the study developed a desktop Virtual Reality product integrated with AI-generated audio narration. Data were collected through interviews, observations, and validation by material, media experts and library practitioner, followed by user trials. Results indicate that the Virtual Reality media is highly feasible, with material validation reaching 88%, media validation at 94% and library practitioner validation at 91%. User trials showed an 91% satisfaction rate, confirming that the Virtual Reality media effectively enhances user understanding of library procedures, such as self-service lockers and circulation. In conclusion, the implementation of Virtual Reality technology provides an immersive, self-directed learning experience that reduces library anxiety and improves operational efficiency for library staff.